Leptosperin is a distinct and detectable fluorophore in Leptospermum honeys. (1st January 2017) - Bong, Jessie; Prijic, Gordana; Braggins, Terry J.; Schlothauer, Ralf C.; Stephens, Jonathan M.; Loomes, Kerry M.
Highlights: Leptosperin is responsible for the unique MM1 fluorescence marker in manuka honey. There is a quenching effect from the honey matrix on leptosperin fluorescence. Leptosperin is chemically stable in honey over prolonged storage at 37 °C. L. subtenue had trace levels of leptosperin compared to other Leptospermum species. Fluorescence spectroscopy offers a method for authenticating Leptospermum honey. Abstract: New Zealand manuka ( Leptospermum scoparium ) honey exhibits two unique fluorescence signatures that distinguish it from other honey types. One of these is the MM1 fluorescence marker (270–365 nm excitation–emission) which we show is due to a Leptospermum nectar-derived compound, leptosperin. Synthetic or honey-purified leptosperin not only displayed an identical fluorescence spectrum, but supplementation of leptosperin into clover or artificial honeys generated the MM1 fluorescence signature. There was a quenching effect of the honey matrix on leptosperin fluorescence but otherwise leptosperin was chemically stable over prolonged storage at 37 °C. Leptosperin was also present in the woody-fruited Australian Leptospermum species at elevated concentrations but virtually absent in Leptospermum subtenue suggesting its elevated expression developed following the mid-Miocene separation of the genus. These findings suggest that fluorescence spectroscopy could offer a rapid and high-throughput screening method for identification of Leptospermum honeys using the MM1 fluorescence marker.